Faktor-Faktor Yang Berhubungan Dengan Pemeriksaan Iva (Inspeksi Visual Asam Asetat) Pada Pus (Pasangan Usia Subur) Di Wilayah Kerja Puskesmas Mataraman Tahun 2020 - Akhmad Rizani (Jurnal Skala Kesehatan, 2021)
IVA examinations in the working area of ​​the Mataraman Health Center decreased from 2018 there were 400 people (9%) from the target of 4,416 to 285 (6%) people from the target of 4,416 in 2019. The factors causing the low VIA examination were influenced by attitude factors, family support (husbands). ), support for health workers and distance to health facilities. The purpose of knowing the factors related to the VIA examination (Visual Inspection of Acetic Acid) at EFA (EU) in the Mataraman working area in 2020. The design of this study was to use the Analytical Survey method and use a Cross Sectional approach. The population in the study were all PUS aged 30-50 years who had had sexual intercourse in the working area of ​​the Mataraman Health Center. The sampling technique in this study is Accidental Sampling. The number of samples in the study was 237 EFA. The research instrument was a questionnaire. Analysis of the data used in this study is the Chi Square statistical test (a = 0.05). The results of the statistical test showed that there was a relationship between attitude (p=0.03), family support (husband) (p=0.03), support from health workers (p=0.001), distance (p=0.119) with VIA examination. Keywords: Attitude, Family Support (Husband), Health Worker Support Distance with VIA Examination.